Pengaruh Model Pembelajaran Inquiry dengan Pendekatan Respect Education terhadap Pencapaian HOTS Siswa - Sriwanda Bouato; Frahmawati Bumulo; Abdulrahim Maruwae; Radia Hafid; Rierind Koniyo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the effect of the Inquiry Learning Model combined with the Respect Education approach on the achievement of Higher Order Thinking Skills (HOTS) of eighth-grade students in the Integrated Social Sciences subject at SMP Negeri 1 Tilamuta. The study employed a quantitative method using a quasi-experimental design. The sample consisted of 65 students. The results indicate that students who were taught using the Inquiry Learning Model showed greater improvement in HOTS achievement compared to those who received Expository Learning Model instruction in the Integrated Social Sciences subject for eighth-grade students at SMP Negeri 1 Tilamuta. This finding is supported by the results of a paired sample t-test, which revealed a significance value (2-tailed) of 0.000 (P < 0.05), confirming a significant difference between the control and experimental groups. Therefore, the inquiry-based learning model, which emphasizes exploration and student autonomy, combined with the Respect Education approach that highlights appreciation of students' potential, is proven effective in improving Higher Order Thinking Skills.